International Corporate Governance Spillovers: Evidence from Cross-Border Mergers and Acquisitions - Albuquerque, Rui; Brandão-Marques, Luis; Ferreira, Miguel A; Matos, Pedro (Review of Financial Studies, 2019)
We test the hypothesis that foreign direct investment promotes corporate governance spillovers in the host country. Using firm-level data from 64 countries during the period 2005–2014, we find that cross-border M&A activity is associated with subsequent improvements in the governance of nontarget firms when the acquirer country has stronger investor protection than the target country. The effect is more pronounced when the target industry is more competitive. Cross-border M&As are also associated with increases in investment and valuation of nontarget firms. Alternative explanations, such as access to global financial markets and cultural similarities, do not appear to explain our findings. Received October 27, 2015; editorial decision March 25, 2018 by Editor Andrew Karolyi. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.